Plasma Needles on the Teeth Structure and Compressibility - Hussein, Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
The aim from this research  is  to prove not affected the teeth of both damage macroscopic and  the internal structure of teeth (compressibility). The teeth were collected from (Al karama dental specialized) in Baghdad, directly after uprooted from the patient's mouth. It was in table by the material (normal saline, sodium chloride, 0.9%), according to instructions of dental disease specialist. It was regarded as a natural model replica. It has been conducted two tests on some samples: studying the macroscopic damage for teeth and studying the influence compressibility for teeth. The design of generation argon plasma needle   system, this system works on production Non- thermal plasma at atmospheric pressure, where used simples electronics constructions and cost low, it has power   to generate high electric field on electrodes enough to ionize different gases and flow in atmospheric pressure. The device jet plasma needle used  surely from  no events any  macroscopic or mechanical damage in build inside teeth (compressibility) ,where it applied  on some teeth sample at time double treatment time ,then teeth check  consequently  favorableness result ,where load  force of tooth without  plasma exposure  was 1.74kN while load  force of tooth with   plasma exposure  was 1.824kN.Studying the macroscopic damage for teeth, the mentioned area were not affected with damage or change colors, therefore in effecting the teeth with any negative results during plasma needle process.
Keywords: necrosis; strain; plasma needle; teeth